Postdisciplinär humanistisk kunskap - Sörlin, Sverker (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
This article presents the ambitions, ongoing since several years, to build an integrated environment for research, education and social engagement in the Division of History of Science, Technology and Environment at the KTH Royal Institute of Technology, Stockholm. The growth and excellence of the Division, it is argued, can be explained by the evolution from the “disciplinary project” of History of Technology in the 1990s into a postdisciplinary environment for historical study.